The involvement of interpreters in psycho-counseling : attitudes of and evaluation by Chinese international students - Zhang, Huanming (Nanyang Technological University, 2020)
Objective: In this study, we aimed to investigate whether the relatively low psycho-counseling participation rate of Chinese international students in Singapore is due to their English proficiency, and what are their attitudes toward the involvement of psychologically trained interpreters in psycho-counseling.